Stability of Hopfield Neural Networks with Delay and Piecewise Constant Argument - Akhmet, M.U.; Karacaören, M. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, by using the concept of differential equations with piecewise constant argument, the model of Hopfield neural networks with constant delay is developed. Sufficient conditions for the existence of an equilibrium as well as its global exponential stability by means of Lyapunov functionals and a linear matrix inequality (LMI) are obtained. An example is given to illustrate our results.